Exploring the miRNA-Mediated Regulation of ERO1L as a Potential Prognostic Biomarker in Cervical Cancer - Eyupoglu, Havva Ozgen; Eyupoglu, Erol; Tuzmen, Sukru (Springernature, 2024)
[Abstract Not Available]
57th Conference of the European-Society-of-Human-Genetics (ESHG) -- JUN 01-04, 2024 -- Berlin, GERMANY